The Effect of E-Recruitment PENGARUH E-RECRUITMENT, EMPLOYER BRAND, COMPANY’S REPUTATION DAN WORK LIFE BALANCE TERHADAP APPLYING FOR JOBS: E-Recruitment, Employer Brand, Company’ S Reputation, Work Life Balance, Applying For Jobs - Sulistyanto, Hari; Bernarto, Innocentius (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Abstract: This research aims to analyze the positive influence of e-Recruitment, employer brand, company reputation and work-life balance on job applications. The sampling method used in this research was convenience sampling. The data collection method uses a questionnaire. The number of respondents was 81 respondents. Data analysis using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The research results show that E-Recruitment, Company's Reputation and Work-Life Balance have a positive effect on Job Applications, while Employer Branding does not have a positive effect on Job Applications